PENGARUH PENAMBAHAN EKSTRAK KULIT BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) TERHADAP KANDUNGAN LEMAK, OKSIDASI LEMAK, DAN AKTIVITAS ANTIOKSIDAN SE’I DAGING SAPI: Effect of Red Dragon Fruit Peel Extract (Hylocereus polyrhizus) Addition on Fat Content, Fat Oxidation, and Antioxidant Activity in Beef Se'i - Asri Yanti; Sulmiyati; Geertruida Margareth Sipahelut; Tri Rizkie Zainal (Faculty of Animal Science, University of Tulang Bawang, 2025)
This study aims to determine the addition of red dragon fruit peel extract (Hyclocereus polyrhizus) to fat content, fat oxidation and antioxidant activity in beef se'i. The materials used were beef thigh muscle, red dragon fruit skin, saltpeter and salt. The method used was experimental method with a completely randomized design (CRD) consisting of 4 treatments and 4 replicates. Treatment P0 without the addition of red dragon fruit peel extract (control), P1 addition of red dragon fruit peel extract 5%, P2 addition of red dragon fruit peel extract 10%, P3 addition of red dragon fruit peel extract 15%. The variables observed were fat content, fat oxidation, and antioxidant activity. Data were analyzed using ANOVA (Analysis of variance) then followed by Duncan's test to determine differences between treatments. The results showed that the addition of red dragon fruit peel extract had a significant effect (P<0.05) on antioxidant activity, while no significant effect (P>0.05) on fat content and fat oxidation. It was concluded that the addition of red dragon fruit peel extract (Hylocereus polyrhizus) at different levels was effective in increasing the antioxidant activity in beef se'i. However, the addition of red dragon fruit peel extract did not show significant effect on fat content and fat oxidation in beef se'i. Keywords: antioxidant, beef se'i, fat content, fat oxidation, red dragon fruit peel